2010
DOI: 10.1111/j.1548-2456.2010.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Partisan Attachment and Democracy in Mexico: Some Cautionary Observations

Abstract: Party identification is a central concept in studies of parties and elections. Drawing from an extensive literature linking the concept of party identification to the understanding of Mexico's electoral politics, this article explores how the Mexican experience informs the understanding of party identification in general, especially in emerging democracies. There, voters' attachments to political parties are usually seen both as essential to and a positive sign of democratic development. This study finds evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the absence of specific data on party members, partisanship in the region has been analyzed through party identification, usually in country-specific studies (McCann and Lawson 2003;Moreno 2003;Morgan 2007;Baker et al 2010;Vidal et al 2010;Samuels and Zucco 2016). When official party membership data is regularly inflated-not only in Latin America (Mair and van Biezen 2001)-public opinion surveys have pointed to rates of party identification that are by no means irrelevant.…”
Section: Party Membership and Activismmentioning
confidence: 99%
“…In the absence of specific data on party members, partisanship in the region has been analyzed through party identification, usually in country-specific studies (McCann and Lawson 2003;Moreno 2003;Morgan 2007;Baker et al 2010;Vidal et al 2010;Samuels and Zucco 2016). When official party membership data is regularly inflated-not only in Latin America (Mair and van Biezen 2001)-public opinion surveys have pointed to rates of party identification that are by no means irrelevant.…”
Section: Party Membership and Activismmentioning
confidence: 99%
“…Over time, these twin trends provide evidence of the Mexican voter's dealignment from the PRI, but as of now, no scholars of Mexico have found realignment through consistent voting with one or another party alternative. Furthermore, newer work explores party identification as an indicator of democratic stability (Medina Vidal et al 2010).…”
Section: Social Group Characteristics and Party Identitymentioning
confidence: 99%
“…Many authors (Beltrán, 2009; Bolívar Meza, 2019; Sánchez y Sánchez, 2019a, 2019b; Vidal et al, 2010) have found that, at least for AMLO's National Regeneration Movement party (Morena) and its coalition in the 2018 elections, there was no clear ideological voter identity (the Social Encounter Party [PES] is actually a pro‐life, right‐wing party, while Morena and the Labor Party [PT] are more left‐leaning). Bolívar Meza (2019, p. 62) notes that, “with the purpose of accumulating more votes and win elections, this coalition did not present a political project based on a specific ideology but instead immediate objectives…this time as a candidate for the coalition [Obrador] kept a moderate posture, placing the fight on corruption as the main aspect of his project.” Likewise, Sánchez y Sánchez (2019a) find that, in Mexico City, those who voted for Morena in 2018, followed a “rational partisanship,” motivated more by the poor performance of the previous mayor (Miguel Angel Mancera, of the Party of the Democratic Revolution [PRD]) and the repercussions of social programs than their views on topics, such as abortion or same‐sex marriage (considered as left‐wing ideology).…”
Section: Introductionmentioning
confidence: 99%
“…Bolívar Meza (2019, p. 62) notes that, “with the purpose of accumulating more votes and win elections, this coalition did not present a political project based on a specific ideology but instead immediate objectives…this time as a candidate for the coalition [Obrador] kept a moderate posture, placing the fight on corruption as the main aspect of his project.” Likewise, Sánchez y Sánchez (2019a) find that, in Mexico City, those who voted for Morena in 2018, followed a “rational partisanship,” motivated more by the poor performance of the previous mayor (Miguel Angel Mancera, of the Party of the Democratic Revolution [PRD]) and the repercussions of social programs than their views on topics, such as abortion or same‐sex marriage (considered as left‐wing ideology). Vidal et al (2010) find that clientelist attachments influence some aspects of party identification in Mexico, while Beltrán (2009) and Sánchez y Sánchez (2019b) show that there are very few ideological voters in Mexico when it comes to their ideas or opinions on specific policies. Moreover, Morena is a party founded by AMLO in 2015 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation